DIGESTIBILITY OF SELECTED FEED INGREDIENTS FOR TIGER GROUPER, Epinephelus fuscoguttatus - Usman Usman; Kevin C. Williams; Mike A. Rimmer (Indonesian Aquaculture Journal, 2007)
The apparent digestibility (AD) of eight feed ingredients are widely available in Indonesia was determined. In each of two 5x5 latin-square experimental, tiger grouper Epinephelus fuscoguttatus juveniles (100—150 g) were fed a reference diet and four test diets in accordance with the latin-square design. Test feed ingredients were substituted at rates of 40% for animal meals or 30% for plant meals. Chromic oxide was used as the digestibility marker. In determining the ingredient AD, the substitution ratio was calculated as the proportion of the nutrient (or energy) contributed by the test ingredient on an ‘as-is’ basis. Digestibility tanks were steeply slope 200 L cylindroconical tanks with a bottom outlet to facilitate faecal collection, which was carried out at 3-hourly intervals throughout the day. Each collection period took 5—7 days with a similar acclimatization time between diets. A combined ANOVA of the data for both experimental showed no difference (P>0.05) in the AD’s for each reference diets. Thus for comparative purpose, the derived AD’s of the test ingredients were analysed as a single ANOVA. The digestibility of animal meals was generally high(>59% for dry matter, >83% for protein, >65% for lipid, and >70 for gross energy) while that of plant meals was slow (<53% for dry matter, <53% for protein, <66% for lipid, and <46% for gross energy). This information will enable grow-out feeds for tiger grouper to be formulated on a least-cost digestible nutrient basis.